2009
DOI: 10.1111/j.1399-0004.2009.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild ring 17 syndrome shares common phenotypic features irrespective of the chromosomal breakpoints location

Abstract: Ring 17 syndrome is a rare disorder with clinical features influenced by the presence or deletion of the Miller-Dieker critical region (MDCR). Presence of the MDCR is associated with a mild phenotype, including growth delay (GD), mental retardation (MR), seizures, cafè au lait skin (CALS) spots and minor facial dysmorphisms. Previous studies have been mainly focused on this locus providing poor information about the role of other genes located on the p- and q-arms. Here, we used bacterial artificial chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…A previous review of all ring chromosome 17 cases, without MDCR involvement, showed shared common phenotypic features with no consistency in copy number losses [Charles et al, 1991;Surace et al, 2009]. This observation is supported by our case which, in comparison to the only 2 other cases with a detailed description of epilepsy, showed a discrepant copy number loss [RicardMousnier et al, 2007;de Palma et al, 2015].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A previous review of all ring chromosome 17 cases, without MDCR involvement, showed shared common phenotypic features with no consistency in copy number losses [Charles et al, 1991;Surace et al, 2009]. This observation is supported by our case which, in comparison to the only 2 other cases with a detailed description of epilepsy, showed a discrepant copy number loss [RicardMousnier et al, 2007;de Palma et al, 2015].…”
Section: Discussionsupporting
confidence: 74%
“…Ring chromosome 17 without MDCR involvement is rare [Qazi et al, 1979;Chudley et al, 1982;Charles et al, 1991;Gass and Taney, 1994;Endo et al, 1999;Shashi et al, 2003;Ricard-Mousnier et al, 2007;Kumari et al, 2009;Surace et al, 2009;de Palma et al, 2015]. Epilepsy, although reported in all cases, is well described in only 2 patients, both presenting with nocturnal focal seizures and prolonged diurnal nonconvulsive status epilepticus [Ricard-Mousnier et al, 2007;de Palma et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several early studies of relevant proteins suggest their potential roles, but a role for Metrnl has not yet been reported. However, the Nterminus of METRNL shows homology with that of meteorin, a secreted protein that is involved in the development of the nervous system and in glial cell differentiation and axonal extension (Nishino et al, 2004;Surace et al, 2009). METRNL might be involved in neurite extension as a secreted protein in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…1 Ring chromosome 17 is a rare genetic abnormality described, to date, in 17 patients. 2 Seizures, mental retardation, skin manifestations, and reduced growth are very common in affected subjects. However, the clinical phenotype is highly variable, and this can be in relation to the deletion size.…”
Section: Questions For Considerationmentioning
confidence: 99%